PENDIDIKAN SELERA DALAM PERKEMBANGAN RESTORAN HINDIA BELANDA DAN RIJSTTAFEL DI BELANDA PADA PERIODE KOLONIAL - Ariwibowo, Andika (Paradigma: Jurnal Kajian Budaya, 2024)
This article discusses the early development of rijsttafel and Dutch East Indies restaurants in the Netherlands during colonial period between the mid-19th and mid-20th centuries. The study takes a closer look at the early development of rijsttafel and Dutch East Indies restaurants in the Netherlands during the colonial period, as well as the role of actors in introducing rijsttafel and Dutch East Indies ethnic food in the Netherlands. This study aims to provide an alternative way of studying the history of culinary and gastronomic development and the influence of Dutch East Indies culture in the Netherlands. The historical sources used are newspapers, cookbooks, and guidebooks on Dutch East Indies cuisine, gastronomy, and restaurants in the Netherlands in the colonial period. The development of rijsttafel and Dutch East Indies restaurants in the Netherlands demonstrates the strong influence of colonial cultural imperialism in diversifying flavors in Europe in the mid-19th to mid-20th centuries. The early trajectory of rijsttafel in the Netherlands also shows that culinary dishes and gastronomic cultures from colonies such as the Dutch East Indies can be adapted and modified into various flavors that suit the tastes of Dutch society.